Karyotype of the yellow-bellied sea snake, Pelamis platurus - Gutiérrez, José María (1980)
In this paper we describe the karyotype of the yellow-bellied sea snake, Pelamis platurus from Costa Rica. The diploid number is 38 chromosomes, with 20 macrochromosomes and 18 microchromosomes. The pairs 1 and 2 are metacentrics, pair 3 is subtelocentric and pairs from 4 to 9 have the centromere in a terminal position. Females have a pair of slightly heteromorphic chromosomes identified as sex chromosomes Z and W; both are metacentrics but have different centromeric index and W is slightly smaller.The pattern of heteromorphism in sex chromosomes and the secondary constriction present in some sea snake karyotypes could be useful parameters in determining evolutionary relationships between the sea snakes.